Construction of eukaryotic expression vector of Interleukin-2 gene from Xiaoshan Chicken and its expression in Vero cells - XIE Rong-hui; FANG Wei-huan; LI Jian-rong; LU Mi-jia; YU Lian (浙江大学学报. 农业与生命科学版)
In previous study IL-2 gene of Xiaoshan Chicken has been cloned by our laboratory, and in this study the cDNA of IL-2 was amplified and inserted into the eukaryotic expression vector pCI. The resulted recombinant plasmid pCI-IL-2 was transformed by electroporation into an attenuated Salmonella typhimurium strain ZJ111, which was then used to transfect Vero cells. DNA extracted from the transfected Vero cells showed a positive signal as hybridized with DIG-labeled probe in a DNA blotting assay, which revealed that the IL-2 gene was integrated into the genome of Vero cells. Specific yellow-green fluorescence was visual in indirect immunofluorescence assay with FITC-labeled goat anti-rabbit IgG. The 14.5 kD and 18.5 kD bands correspond to IL-2 protein from lysate of Vero cells was identified by SDS-PAGE and Western blotting, indicating that in Vero cells IL-2 was expressed successfully with the characteristics of immunological reactivity.